Co-Pyrolysis Upgrading of High-Ash Biogas Residue with Lignocellulosic Biomass: Synergistic Kinetics, Energy Enhancement, and EBC-Compliant Biochar Production - Chung-Liang Chang; Minh Phu Nguyen; Hong-Kai Li; Chin-Chao Chen; Chyi-How Lay; Chiu-Yue Lin (BioEnergy Research, 2026)

Assessing energy poverty alleviation, energy security enhancement, and decent work and economic growth in China under SDGs 7 and 8: A meta parallel two-stage dynamic SBM-DEA analysis - Li Ji; Yung-ho Chiu; Tzu-Han Chang; Li Yang; Hsiang-Yue Chen (Journal of Cleaner Production, 2026)

A scalable consensus docking decision-support pipeline for aquaculture bridging foodomics and affordability - Chen-Hsun Liu; Chiu-Hui Kuo; William Chih-Wei Chang; Chih-Hsuan Fan; Bonien Chen; Li-Lian Liu; Fen-Chen Wu; Pao-Chi Liao; Kuohsun Chiu (Computers and Electronics in Agriculture, 2026)

Integrating deep learning and groundwater dynamics for drought vulnerability assessment under climate scenarios - Wei Sun; Li-Chiu Chang; Jun Jie Lin; Fi-John Chang (Groundwater for Sustainable Development, 2026)

Integrated Multi-Endpoint Analysis of Soluble Copper(II) Chloride–Induced Oxidative Stress, Mitochondrial Dysfunction, and Genotoxicity in RAW264.7 Macrophages - Ping-Kun Tsai; Sheng-Wen Wu; Yen-Ju Lee; Yu-Ting Chang; Shiuan-Shinn Lee; Yung-Chuan Ho; Li-Chiu Yang; Yu-Hsiang Kuan (Biological Trace Element Research, 2026)

Thermal resistance and stability of multilayers embedding probiotic structure - Ping-Hsiu Huang; Chien-Shan Chiu; Wen-Chien Lu; Chang-Wei Hsieh; Po-Hsien Li (Journal of Food Engineering, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Advanced groundwater level forecasting with hybrid deep learning model: Tackling water challenges in Taiwan’s largest alluvial fan - Yu-Wen Chang; Wei Sun; Pu-Yun Kow; Meng-Hsin Lee; Li-Chiu Chang; Fi-John Chang (Journal of Hydrology, 2025)

AI-driven weather downscaling for smart agriculture using autoencoders and transformers - Pu-Yun Kow; Yun-Ting Wang; Yu-Wen Chang; Meng-Hsin Lee; Ming-Hwi Yao; Li-Chiu Chang; Fi-John Chang (Computers and Electronics in Agriculture, 2025)

Flood resilience through hybrid deep learning: Advanced forecasting for Taipei's urban drainage system - Li-Chiu Chang; Ming-Ting Yang; Fi-John Chang (Journal of Environmental Management, 2025)

An eigen-based theory for developing numerical methods for structural dynamics - Chiu-Li Huang; Shuenn-Yih Chang; Karen Chang (Earthquake Engineering and Engineering Vibration, 2025)

Seasonality and extreme flooding can override the effects of debris dam removal on riverine species: a case study of macroinvertebrates - Tsung-Tse Hsieh; Jia-Yi Li; Che-Chang Lin; Mei-Hwa Kuo; Ming-Chih Chiu (Aquatic Ecology, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

Methane degassing in global river reservoirs and its impacts on carbon budgets and sustainable water management - Yanlai Zhou; Hanbing Xu; Tianyu Xia; Lihua Xiong; Li-Chiu Chang; Fi-John Chang; Chong-Yu Xu (Science of The Total Environment, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Advancing climate-resilient flood mitigation: Utilizing transformer-LSTM for water level forecasting at pumping stations - Pu-Yun Kow; Jia-Yi Liou; Ming-Ting Yang; Meng-Hsin Lee; Li-Chiu Chang; Fi-John Chang (Science of The Total Environment, 2024)

Deep dive into predictive excellence: Transformer's impact on groundwater level prediction - Wei Sun; Li-Chiu Chang; Fi-John Chang (Journal of Hydrology, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Reassessment of industrial eco-efficiency in China under the sustainable development goals: A meta two-stage parallel entropy dynamic DDF-DEA model - Li Yang; Shiying Chen; Yung-ho Chiu; Tzu-Han Chang; Yue Wang (Journal of Cleaner Production, 2024)

Existing levels of biodiversity and river location may determine changes from small hydropower developments - Qingyi Luo; Shuyin Li; Tsuyoshi Kinouchi; Naicheng Wu; Xiaocheng Fu; Chang Ling; Qinghua Cai; Ming-Chih Chiu; Vincent H. Resh (Journal of Environmental Management, 2024)

Oxidative stress and potential effects of metal nanoparticles: A review of biocompatibility and toxicity concerns - Yung-Li Wang; Yu-Hsuan Lee; Chu-Lin Chou; Yu-Sheng Chang; Wen-Chih Liu; Hui-Wen Chiu (Environmental Pollution, 2024)

Dynamic efficiency evaluation of electric power and environmental treatment efficiency in China - Y. Li; Y. Chiu; T.-Y. Lin; S.-M. Wang; T.-H. Chang (International Journal of Environmental Science and Technology, 2024)

Reassessment of the efficiency of China's industrial circular economy considering quality of life: a meta recycle SBM dynamic under exogenous model - Anqi Lei; Li Yang; Yung-ho Chiu; Yuan-yuan Niu; Tzu-Han Chang (Environment, Development and Sustainability, 2024)

Photocurable 3D-printed AgNPs/Graphene/Polymer nanocomposites with high flexibility and stretchability for ECG and EMG smart clothing - Jia-Wun Li; Ho-Fu Chen; Yu-Zhe Liu; Jui-Hsin Wang; Ming-Chang Lu; Chih-Wei Chiu (Chemical Engineering Journal, 2024)

Watershed groundwater level multistep ahead forecasts by fusing convolutional-based autoencoder and LSTM models - Pu-Yun Kow; Jia-Yi Liou; Wei Sun; Li-Chiu Chang; Fi-John Chang (Journal of Environmental Management, 2024)

High-spatiotemporal-resolution PM2.5 forecasting by hybrid deep learning models with ensembled massive heterogeneous monitoring data - Kuan-Yen Wu; I-Wen Hsia; Pu-Yun Kow; Li-Chiu Chang; Fi-John Chang (Journal of Cleaner Production, 2023)

A flood Impact-Based forecasting system by fuzzy inference techniques - Gary Wee; Li-Chiu Chang; Fi-John Chang; Mohd Zaki Mat Amin (Journal of Hydrology, 2023)

An Innovative Designed Velocimeter Application for Set Net Fishery - Cheng-Chang Chiu; Teh-Lu Liao; Chiung-Hsing Chen; Hsiang Li (Journal of Marine Science and Engineering, 2023)
This article is aimed at the problems encountered by the fishing ground of set nets in Taiwan when the set net operators need to work when the weather is bad at sea. We developed a velocimeter that can be placed in the ocean for a long time and change sensing directions with the flow direction. The self-designed velocimeter has advantages, such as simple operation, low cost, and easy maintenance. With wireless monitoring and an early warning system, it can monitor current velocity, flow direction, sea temperature, and displacement. The data is transmitted back to the operator through the radio transmission module as a basis for dispatching personnel to go out to sea for fishing. To prevent the set net from drifting into the open sea due to bad weather, a GPS module is used to monitor the current location of the set net. If the waves wash away the set net, the warning signal can be received the first time to prevent the floating set net from endangering the safety of ship navigation and the survival of marine life. This innovative technology aligns with SDG 14, which aims to “conserve and sustainably use the oceans, seas, and marine resources for sustainable development”.

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Explore Regional PM2.5 Features and Compositions Causing Health Effects in Taiwan - Yi-Shin Wang; Li-Chiu Chang; Fi-John Chang (Environmental Management, 2021)

Relationships among cigarette smoking, urinary biomarkers, and urothelial carcinoma risk: a case-control study - Chi-Jung Chung; Hui-Tsung Hsu; Chao-Hsiang Chang; Sheng-Wei Li; Chiu-Shong Liu; Mu-Chi Chung; Guo-Wei Wu; Wei-Ting Jung; Yen-Jung Kuo; Hui-Ling Lee (Environmental Science and Pollution Research, 2020)

Anti-hypertensive effects of Radix Rehmanniae and its active ingredients - Chiu-Haw Chao; Jue-Liang Hsu; Mu-Fen Chen; Ya-Hu Shih; Chia-Hui Lee; Mei-Li Wu; Chi-I Chang (Natural Product Research, 2020)

Epirubicin induces apoptosis in osteoblasts through death-receptor and mitochondrial pathways - Tzu-Ching Huang; Pu-Rong Chiu; Wen-Tsan Chang; Bau-Shan Hsieh; Yu-Ci Huang; Hsiao-Ling Cheng; Li-Wen Huang; Yu-Chen Hu; Kee-Lung Chang (Apoptosis, 2018)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Use of cardioselective β-blockers and overall death and cardiovascular outcomes in patients with COPD: a population-based cohort study - Yaa-Hui Dong; Chia-Hsuin Chang; Li-Chiu Wu; Mei-Shu Lai (European Journal of Clinical Pharmacology, 2016)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

Investigating the interactive mechanisms between surface water and groundwater over the Jhuoshuei river basin in central Taiwan - Fi-John Chang; Cheng-Hsien Lin; Kuang-Chih Chang; Yu-Hsuan Kao; Li-Chiu Chang (Paddy and Water Environment, 2014)

Better environmental data may reverse conclusions about niche‐ and dispersal‐based processes in community assembly - Li-Wan Chang; David Zelený; Ching-Feng Li; Shau-Ting Chiu; Chang-Fu Hsieh (Ecology, 2013)
Variation partitioning of species composition into components explained by environmental and spatial variables is often used to identify a signature of niche‐ and dispersal‐based processes in community assembly. Such interpretation, however, strongly depends on the quality of the environmental data available. In recent studies conducted in forest dynamics plots, the environment was represented only by readily available topographical variables. Using data from a subtropical broad‐leaved dynamics plot in Taiwan, we focus on the question of how would the conclusion about importance of niche‐ and dispersal‐based processes change if soil variables are also included in the analysis. To gain further insight, we introduced multiscale decomposition of a pure spatial component [c] in variation partitioning. Our results indicate that, if only topography is included, dispersal‐based processes prevail, while including soil variables reverses this conclusion in favor of niche‐based processes. Multiscale decomposition of [c] shows that if only topography was included, broad‐scaled spatial variation prevails in [c], indicating that other as yet unmeasured environmental variables can be important. However, after also including soil variables this pattern disappears, increasing importance of meso‐ and fine‐scaled spatial patterns indicative of dispersal processes.

Inhibition of Japanese Encephalitis Virus Infection by the Sulfated Polysaccharide Extracts from Ulva lactuca - Ya-Huang Chiu; Yi-Lin Chan; Tsung-Lin Li; Chang-Jer Wu (Marine Biotechnology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

TCF7L2 genetic variants and progression to diabetes in the Chinese population: pleiotropic effects on insulin secretion and insulin resistance - Yi-Cheng Chang; Yen-Feng Chiu; Larry Low-Tone Ho; Chih-Tai Ting; Kuang-Chung Shih; J. David Curb; Yii-Der Ida Chen; Hung-Yuan Li; Lee-Ming Chuang (Journal of Molecular Medicine, 2010)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Characterizinig Precipitation Chemistry in Changhua, Central Taiwan Using Weather Conditions And Multivariate Analysis - Chuan-Te Chang; Teng-Chiu Lin; Mei-Li Hsueh (Water, Air, & Soil Pollution, 2005)

Transgenic tomato plants expressing an Arabidopsis thionin (Thi2.1) driven by fruit-inactive promoter battle against phytopathogenic attack - Yuan-Li Chan; Venkatesh Prasad; Sanjaya; Kuei Hung Chen; Po Chang Liu; Ming-Tsair Chan; Chiu-Ping Cheng (Planta, 2005)

Allelopathic Potential of Acacia confusa and Related Species in Taiwan - Chang-Hung Chou; Chiu-Yu Fu; Shin-Yi Li; Yu-Fa Wang (Journal of Chemical Ecology, 1998)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)